2020
DOI: 10.1525/collabra.349
|View full text |Cite
|
Sign up to set email alerts
|

Disgust, Anger, and Aggression: Further Tests of the Equivalence of Moral Emotions

Abstract: People often report disgust toward moral violations. Some perspectives posit that this disgust is indistinct from anger. Here, we replicate and extend recent work suggesting that disgust and anger toward moral violations are in fact distinct in terms of the situations in which they are activated and their correspondence with aggressive sentiments. We tested three hypotheses concerning emotional responses to moral violations: (1) disgust is associated with lower-cost, indirectly aggressive motives (e.g., gossip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
3
21
1
Order By: Relevance
“…In a series of preregistered studies, we repeatedly replicated and extended prior work rooted in the premise that natural selection has shaped emotional reactions to moral transgressions to contingently track the fitness incentives of direct aggression. It should come as little surprise that Molho et al's (2017) findings proved generally robust, given that their original studies were also publicly archived, and have been largely conceptually replicated in a recent preregistered study (Tybur et al, 2019). Replications which incorporate straightforward theoretical extensions, as we have pursued here, hold particular promise in building a cumulative science.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In a series of preregistered studies, we repeatedly replicated and extended prior work rooted in the premise that natural selection has shaped emotional reactions to moral transgressions to contingently track the fitness incentives of direct aggression. It should come as little surprise that Molho et al's (2017) findings proved generally robust, given that their original studies were also publicly archived, and have been largely conceptually replicated in a recent preregistered study (Tybur et al, 2019). Replications which incorporate straightforward theoretical extensions, as we have pursued here, hold particular promise in building a cumulative science.…”
Section: Discussionmentioning
confidence: 61%
“…As anticipated, they found that immoral harms to the self elicited greater anger, which in turn predicted greater motivation to directly aggress against the transgressor, than did the same harms inflicted on an acquaintance. Conversely, transgressions against acquaintances evoked greater feelings of disgust, and disgust was positively correlated with inclinations to indirectly aggress (for a preregistered conceptual replication, see Tybur et al, 2019).…”
mentioning
confidence: 99%
“…While anger is associated with approach-oriented, aggressive behaviors (68,118,119), disgust has been seen as motivating social avoidance (95,117,120) and efforts to signal condemnation to third parties (93,121). Consistent with these ideas, multiple vignette studies have shown that anger in response to offenses is specifically associated with inclinations to punish offenders directly, via physical and verbal confrontation (92,93,122). In contrast, moral disgust in response to the same offenses is associated with inclinations to punish offenders indirectly, via gossip and ostracism.…”
Section: Emotions As Proximate Motivators Of Punishmentmentioning
confidence: 89%
“…While anger is associated with approach-oriented, aggressive behaviours [69,118,119], disgust has been seen as motivating social avoidance [96,117,120] and efforts to signal condemnation to third parties [94,121]. Consistent with these ideas, multiple vignette studies have shown that anger in response to offences is specifically associated with inclinations to punish offenders directly, via physical and verbal confrontation [93,94,122]. By contrast, moral disgust in response to the same offences is associated with inclinations to punish offenders indirectly, via gossip and ostracism.…”
Section: (C) Emotions As Proximate Motivators Of Punishmentmentioning
confidence: 98%